British policy towards Muslims and its impact on the administration of Islam in the Federated Malay States, 1874-1920s - Zakariya, Hafiz (Journal of Humanities, Language, Culture and Business, 2019)
The late nineteenth century marked the beginning of British policy of intervention in the Malay states with the signing of the landmark Pangkor Treaty in 1874. The imposition of British power in Malaya brought about radical changes in many spheres of life: demography, economy, law and politics. This article describes the historical background of the imposition of British suzerainty in Malaya, and the development of Islamic beliefs and practice in colonial Malaya. It focuses on two important issues; namely British policy on Islam and the development of Islamic bureaucracy in the Federated Malay States. This study contends that British adopted a cautious approach in dealing with Muslim matters in the Malay states, so as to ensure its policy did not offend the sensitivities of the Malays. British interference in the Malay States marked the seizure of the political power from the Malay sultans. In response to the abrupt decline of their political power, the Malay sultans in the Federated Malay States were left with authority over matters concerning religion (Islam) and Malay customs only. Thus, accordingly, the sultans embarked upon the establishment and consolidation of well-organised Islamic bureaucracy in the Federated Malay States.